Trophic overlap between non‐native brown bullhead (Ameiurus nebulosus) and native shortfin eel (Anguilla australis) in shallow lakes. Issue 4 (10th April 2018) - Collier, Kevin J.; Pingram, Michael A.; Francis, Laura; Garrett‐Walker, Jeremy; Melchior, Michele
Abstract: We quantified trophic overlap between the invasive, non‐native catfish brown bullhead ( Ameiurus nebulosus ) and the New Zealand native shortfin eel ( Anguilla australis ) in four peat and riverine lakes using stable isotope (δ 13 C and δ 15 N) and gut content analyses. Across all lakes and fish sizes over the austral spring–summer period, shortfin eel guts were dominated numerically by fish prey (57% occurrence cf 42% in brown bullhead), while Diptera larvae were most commonly encountered in guts of brown bullhead (45% cf 14% in eels). Significant differences in % composition of animal contents in guts were detected between fish species and sampling occasions ( n  =   4) but not between lakes. In contrast, stable isotope signatures of brown bullhead and shortfin eel did differ significantly between lakes but not between sampling occasions, indicating enduring sources of nutrition despite apparently differing ingestion patterns over time. The R mixing model MixSIAR indicated that shortfins likely assimilated higher proportions of fish prey carbon compared to brown bullheads, which appeared to show greater assimilation of invertebrates, consistent with the results of gut content analyses. Isotopic niche regions, calculated in nicheROVER using probabilistic ellipses, indicated that shortfin eels occupied at least c.60% of brown bullhead trophic niche, which occupied less than 30% of eel trophic niche in all but one lake. These estimates suggest that brown bullhead has higher potential to influence shortfin eel nutrition than vice versa, or that a broad trophic niche occupied by eels provides resilience to the effects of overlapping consumption patterns with invasive omnivores.